Gene therapy in hereditary retinal dystrophy - Jia-Ying Chien; Shun-Ping Huang (Tzu-Chi Medical Journal, 2022)
Hereditary retinal dystrophies (HRDs), such as retinitis pigmentosa, Leber's congenital amaurosis (LCA), Usher syndrome, and retinoschisis, are a group of genetic retinal disorders exhibiting both genetic and phenotypic heterogeneity. Symptoms include progressive retinal degeneration and constricted visual field. Some patients will be legal or completely blind. Advanced sequencing technologies improve the genetic diagnosis of HRD and lead to a new era of research into gene-targeted therapies. Following the first Food and Drug Administration approval of gene augmentation therapy for LCA caused by RPE65 mutations, multiple clinical trials are currently underway applying different techniques. In this review, we provide an overview of gene therapy for HRD and emphasize four distinct approaches to gene-targeted therapy that have the potential to slow or even reverse retinal degeneration: (1) viral vector-based and nonviral gene delivery, (2) RNA-based antisense oligonucleotide, (3) genome editing by the Clustered Regularly Interspaced Short Palindromic Repeat/cas9 system, and (4) optogenetics gene therapy.